Active control on flow-induced vibration of the head gimbals assembly in hard disk drives - Min, H. (2013)
A feedback active method is proposed to control the flow-induced vibration (FIV) of the head gimbals assembly (HGA) through suppressing the pressure fluctuations around the HGA. Firstly pressure fluctuations and FIV measurements are carried out around the HGA in a working hard disk drive, and the results show a high correlationship between the spectra of the HGA's FIV and the pressure fluctuations. Secondly numerical simulations are conducted to investigate the control effect on the HGA's FIV by the proposed feedback active method with a pressure virtual sensing architecture. The numerical results show that the HGA's FIV can be successfully controlled through suppressing the pressure fluctuations with virtually sensing pressure in the wake zone of the HGA.